Flow transitions in collisions between vortex-rings and density interfaces - Yeo, Kye Wei B. (2022)
Flow transitions and vortical developments during vortex-ring collisions with a sharp water–oil density interface are studied using planar laser-induced fluorescence and time-resolved particle-image velocimetry techniques. Circular vortex-rings at Reynolds numbers of Re = 1000 , 2000 and 4000 colliding with a density interface characterized by an Atwood number of approximately A= 0.045 were investigated. Results show that at Re = 1000 , collision with the density interface produces vortical structures and flow transitions that are relatively similar to those for a solid-boundary collision. However, the dynamics underlying the present vortical formations and behaviour are different from those associated with solid-boundary collisions, in that the former are driven by baroclinic vorticity generation. Flow behaviour at Re = 2000 shows more significant deformation of the density interface by the vortex-ring but overall behaviour remains comparable. Last but not least, at Re = 4000 , the largest Reynolds number investigated here, the vortex-ring penetrates the density interface almost completely. However, buoyancy effects eventually limit its penetration and reverse its translational direction, such that it crosses back into the oil layer again with its vortex core rotational senses reversed as well. At the same time, vortex-ring fluid is shed and a significant trailing-jet is left in the former’s wake.